Sustainability Report and Integrated Report: A Comprehensive Comparison - Mahmud, Md Tapan (AIUB Journal of Business and Economics, 2018)
To align with the environmental and societal changes, firms are now offering both financial and non-financial information in their reports. For providing non-financial information (ESG: environmental, social, governance) Sustainability Report (SR) and Integrated Report (IR) are the ‘go to’ channels for the firms; in the evolutionary process of corporate reporting these are the latest additions. Interestingly, even if both these reports offer non-financial information, they hold few contrasts between each other. On the said note, this paper tries to portray a comprehensive comparison between SR and IR. Focus of SR is to provide non-financial information for a wide range of stakeholders, it is mostly based on standards, it has a subjective approach and its industry customization is moderate. Conversely, IR provides non-financial information mostly for the providers of financial capital, it is principle based, has an objective approach and holds high level of industry customization. However, both platforms suffer from lack of assurance, comparability and legal support. Future studies can be initiated to solve these issues. Additionally, IR and SR will face imminent challenges sourcing from climate change, human rights issues, wealth inequality and data & technology advancement. Report preparers and academics may draw conceptual framework regarding the configuration of IR and SR, from this study.